Atypical delayed auditory feedback effect and Lombard effect on speech production in high-functioning adults with autism spectrum disorder - Lin, I-Fan; Mochida, Takemi; Asada, Kosuke; Ayaya, Satsuki; Kumagaya, Shin-ichiro; Kato, Masaharu (Frontiers in Human Neuroscience, 2015)
Individuals with autism spectrum disorder (ASD) show impaired social interaction and communication, which may be related to their difficulties in speech production. To investigate the mechanisms of atypical speech production in this population, we examined feedback control by delaying the auditory feedback of their own speech, which degraded speech fluency. We also examined feedforward control by adding loud pink noise to the auditory feedback, which led to increased vocal effort in producing speech. The results of Japanese speakers show that, compared with neurotypical individuals, high-functioning adults with ASD (including Asperger's disorder, autistic disorder, and pervasive developmental disorder not otherwise specified) were more affected by delayed auditory feedback but less affected by external noise. These findings indicate that, in contrast to neurotypical individuals, those with ASD relied more on feedback control than on feedforward control in speech production, which is consistent with the hypothesis that this population exhibits attenuated Bayesian priors.